Enhanced Vestibulo-Ocular Reflex Responses on vHIT. Is It a Casual Finding or a Sign of Vestibular Dysfunction? - Rey-Martinez, Jorge; Burgess, Ann M.; Curthoys, Ian S. (Frontiers in Neurology, 2018)
In the actual clinical practice, when on a vHIT testing it is observed that eye responses velocities are significantly higher than head movement velocity during slow phase the vHIT it is considered that the most probable causes for this finding are an inadequate collection method or a recording artefact. We present two cases with clinical diagnose of Ménière Disease, for both cases, enhanced eye velocity responses were measured with a rigorous vHIT testing protocol. In one of the cases we measured these enhanced responses on each of the measurements performed during a five-year time series and on the second case multiple measurements were also obtained from a patient after the radiologic diagnosis of vestibulo-cochlear hydrops. The two cases presented and the new evidences reported by other researches suggests that due the low probability of artefact and the high consistence of the vHIT measurements the hypothesis of a physio-pathologic cause should be considered as cause of enhanced eye responses on the vHIT testing of some patients with vestibular dysfunction.